2017
DOI: 10.1080/08276331.2017.1327565
|View full text |Cite
|
Sign up to set email alerts
|

Munificence contingent small business growth model (special emphasis to African SMEs’ context)

Abstract: Classifications:B. Functional management and growth of an SME; C. Strategic management and change in an SME; Factors of success and failure in SME and entrepreneurial firms; Growth of SMEs; Managing change in an uncertain and changing environment Abstract:Despite the growth in number and kind of research emphasizing small and medium-sized enterprises (SMEs), little is known about the relationship between drivers and modes of SMEs' growth. To address this gap, the paper systematically analyzes the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
1
6
0
1
Order By: Relevance
“…This study has shown that business networking has a positive and significant relationships with entrepreneurial munificence. The findings of this investigation complement those of recent research by Alemayehu & Vuuren (2017) and Long & Dong (2017) who reported that small business will tend to collaborate more in munificence environment when the entrepreneurial resources are in abundance. It is suggested that small and micro enterprise technology based rural business need to develop collaborative https: //dx.doi.org/10.15405/epsbs.2018.07.02.86 Corresponding Author: Othman Chin Selection and peer-review under 828 strategies with other firms and relevant governmental agencies to grab the opportunities available in a munificence environment.…”
Section: Resultssupporting
confidence: 86%
“…This study has shown that business networking has a positive and significant relationships with entrepreneurial munificence. The findings of this investigation complement those of recent research by Alemayehu & Vuuren (2017) and Long & Dong (2017) who reported that small business will tend to collaborate more in munificence environment when the entrepreneurial resources are in abundance. It is suggested that small and micro enterprise technology based rural business need to develop collaborative https: //dx.doi.org/10.15405/epsbs.2018.07.02.86 Corresponding Author: Othman Chin Selection and peer-review under 828 strategies with other firms and relevant governmental agencies to grab the opportunities available in a munificence environment.…”
Section: Resultssupporting
confidence: 86%
“…Although the strategy was proclaimed to promote market and customer expansion, it seems to have implications for rural SMMEs in South Africa in general and in the study area in particular, since they are characterized by inadequate resources, and the strategy's implementation could deplete the scarce resources, leading to the SMMEs stagnation or collapse. The above results are not surprising, since it can be explained that this strategy is also dependent on the prevailing economic environment, which in most cases must be favorable (Alemayehu and Van Vuuren, 2017). The environment of the surveyed SMMEs is not favorable.…”
Section: Discussionmentioning
confidence: 77%
“…The favorable economic environment encourages SMEs to cooperate with other businesses through diversification strategies (Alemayehu and Van Vuuren, 2017), whereby SMMEs offer new products to new markets (Ansoff, 2008;Johnson et al, 2008). This strategy is complex in implementation (Veseli et al, 2012), since a business enters markets in which it has little or no experience.…”
Section: Cemj 101mentioning
confidence: 99%
See 1 more Smart Citation
“…En línea con lo anterior, la disponibilidad de recursos que ofrece el entorno, en el cual opera la empresa, es fundamental para generar crecimiento (Todd, Javalgi y Grossman, 2014). Bajo este mismo punto de vista, otra investigación determinó que una empresa puede adoptar 4 avenidas de crecimiento, en función al entorno y a la cantidad de recursos con los que cuente (Alemayehu y van Vuuren, 2017).…”
unclassified